Kemiskinan Multidimensi Anak Di Sumatera Barat: Tinjauan Multiple Overlapping Deprivation Analysis (Moda) Dalam Kerangka Sdgs - Kartika Eka Pratiwi; Nurlatifah (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2026)
This study analyzes child multidimensional poverty in West Sumatra Province in 2024 using the Multiple Overlapping Deprivation Analysis (MODA) approach based on March Susenas data. Child poverty is a critical issue due to its long-term implications for future generations and the achievement of Sustainable Development Goals (SDGs), especially target 1.2. The study aims to measure the prevalence of child deprivation across key rights-based indicators and to identify overlapping patterns across deprivation dimensions. The analysis includes prevalence assessment, overlap mapping, and multidimensional poverty measurement using a cut-off of k = 3. The results indicate that 45.25 persen of children aged 0–17 in West Sumatra are multidimensionally poor, with an average deprivation intensity of 50.78 persen, yielding a Multidimensional Child Poverty Index (Mo) of 22.98 persen. Children aged 0–4 mostly face overlapping deprivations in health, housing, and nutrition, while children aged 5–17 are more likely to experience deprivations in housing, nutrition, and sanitation. These findings emphasize the need for age- and region-sensitive policy interventions that are cross-sectoral and focused on fulfilling children's rights comprehensively.